Superhydrophobic MOFs modified by rosin acid with excellent stability for oil-water separation and catalysis - Siya Guo; Siwei Dai; Junkai Fang; Qingfang Xiong; Yucheng Zhou; Wenting Wang; Min Zhang; Chuntao Kuang; Guoen Yang; Zhaoshuang Li (Journal of Water Process Engineering, 2026)

Computationally tailoring the adsorption behavior of ZrSe2 for SF6 decomposition species in GIS: Mechanistic insights into Cu2O/Ag2O functionalization - Liwen Zhou; Feng Yang; Yingang Gui; Jiagui Tao; Jie Li; Jitao Zhang; Qingfang Zhang; Gang Wei; Zhengqin Cao; Qianglong Yang (Environmental Research, 2026)

A novel method of determining optimal GNSS station density for NWP - Qingzhi Zhao; Qingfang Chen; Yongjie Ma; Haojie Li; Anbang Wu; Ming Liu; Yibin Yao; Hong Liang; Hongwu Guo; Yuxing Zhao; Jing Yang; Qingyuan Guo; et al. (Advances in Space Research, 2026)

Rhodococcus erythropolis KB1 enhances remediation of n-hexadecane pollution by regulating indigenous microbial communities in desert soil - Dan Luo; Siyi Wang; Yanwu Yang; Jianhu Wang; Jixiang Chen; Tianfeng Wang; Yonggang Wang; Qingfang Zhang (Journal of Environmental Chemical Engineering, 2026)

Intrinsic, Cu-, Ag-, and Au-modified Janus NbSSe for detection of SF6 decomposition harmful gases: DFT calculations and gas-sensing mechanism verification - Qianglong Yang; Yingang Gui; Jie Li; Jiagui Tao; Jitao Zhang; Qingfang Zhang (Journal of Environmental Chemical Engineering, 2026)

Waterlogging-induced wheat yield loss is reduced by ditch-buried straw return via increasing soil water infiltration and enhancing plant tolerance - Qingfang Luo; Yuekai Wang; Xinhu Guo; Yue Zhang; Zhenzhen Li; Yanling Li; Fengmin Li; Haishui Yang (Plant and Soil, 2026)

Characterization, antioxidant effects of Lycium ruthenicum Murr. Polysaccharides and protective effects against Oxaliplatin-induced peripheral neurotoxicity through inhibition of the RAS – RAF – MEK – ERK signaling pathway - Limei Wen; Taotao Xue; Yali Guo; Yangchen Wang; Qiang Hou; Ruoyu Geng; Chong Ma; Nan Ding; Jinjin Chen; Qingfang Xue; JunPing Hu; Jianhua Yang (Food Research International, 2026)

Optimizing fertilizer and planting density to stabilize yields and improve water use efficiency in rain-fed wheat–maize rotations - Xueni Yang; Shujie Sun; Haocong Li; Ziyan Guo; Chi Ma; Bo Liu; Wei Zhang; Ruixia Ding; Peng Zhang; Tiening Liu; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2026)

Monoatomic copper anchored on tubular carbon nitride with high carbon/oxygen abundance via 2-methylimidazole direction: synthesis and catalytic performance - Jianghe Chen; Qingfang Zhang; Xia Zhao; Tianfeng Wang; Yabin Li; Zuoyan Chen; Wenjing Xu; Linhai Yang (Environmental Geochemistry and Health, 2026)

Experimental and theoretical study on the eccentric compressive behavior of tie-reinforced CFNRST columns - Xinlei Lv; Qingfang Lv; Yang Qian; Yujie Lu (Engineering Structures, 2025)

Dammarane triterpenoids with anti-inflammatory and promoting glucose uptake activities from the leaves of Cyclocarya paliurus - Xiaoqin Liang; Qingfang Zheng; Biqun Zou; Yanqin Li; Liwei Pan; Chenyang Ren; Jiwen Xin; Bo Yang; Ruiyun Yang; Weifeng Xu; Chaowen He; Yanling Cui; et al. (Phytochemistry, 2025)

Ultrasound-assisted phosphorylation on the functional and structural properties of fish gelatin - Qingfang Ying; Bin Hu; Yijia Li; Liangying Xu; Wenge Yang; Shengnan Zhan; Changrong Ou; Tao Huang (Food Hydrocolloids, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Adaptive fertilization strategies for premature senescence challenges in film-mulched maize: Insights from a 4-year field study - Haixiang Xiong; Chi Ma; Shujie Sun; Ziyi Wang; Ji Zhao; Chun Zhang; Lin Yang; Zhaoyun Dong; Zhikuan Jia; Dan Liu; Qingfang Han; Xudong Zhang (European Journal of Agronomy, 2025)

High-temperature pressure cooking on the quality of Basa (Pangasius bocourti) fish maw: Gelling, in vitro digestion and proteomic analysis - Shiyu Wu; Qiuyu Lu; Lianying Xu; Shengnan Zhan; Wenge Yang; Qingfang Ying; Haixia Yu; Ying Liu; Tao Huang (Food Chemistry, 2025)

Synthesis of tubular amorphous nickel-doped g-C₃N₄ catalyst via pre-assembly strategy for fenton-like oxidation of phenol in wastewater - Qingfang Zhang; Jianghe Chen; Yuxin Zhou; Jianpeng Zhang; Xiangjing Zhang; Tianfeng Wang; Zuoyan Chen; Linhai Yang (Journal of Environmental Chemical Engineering, 2025)

Correction to: Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Cytoglobin augments ferroptosis through autophagic degradation of ferritin in colorectal cancer cells - Chengjiang Fan; Ziyang Luo; Qingfang Zheng; Yuhang Xu; Yao Xu; Jianing Chen; You Meng; Haizhong Jiang; Kaitai Liu; Yang Xi (Molecular and Cellular Biochemistry, 2025)

Air nanobubble simultaneously enhances hydrolysis and methane yield of sludge temperature phased-anaerobic digestion - Ziying Xu; Tianfeng Wang; Cheng Peng; Yutong Feng; Xin Fan; Xuan Yang; Wenqi Gao; Qingfang Zhang (Bioresource Technology, 2025)

Structural characterization of modified straw combined with CPAM conditioned sludge filter cake and analysis of its structure-performance relationship with sludge dewatering performance - Qiyong Yang; Yanbin Zhao; Qingfang Zhang; Ji Wang; Bingjie Xu; Xinhua Zhang; Houfeng Xiong; Han Zhou; Ruimin Xiao (Journal of Environmental Chemical Engineering, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

Transcriptome analysis of human spermatozoa with different DNA fragmentation index using RNA sequencing - Kailin Yang; Xue Sun; Qiyuan Zheng; Chen Pan; Siyuan Wang; Qingfang Lu; Changlong Xu; Yangqing Lu (Reproductive Biology, 2024)

Fault Characteristics and Reservoir Potential of Mesozoic Basins in the Southern East China Sea - Yanqiu Yang; Chuansheng Yang; Jing Sun; Jie Liang; Qingfang Zhao; Jianqiang Wang (Journal of Marine Science and Engineering, 2024)
The East China Sea Basin (ECSB) is an integral part of the Western Pacific tectonic system. Its development is linked to the Kula–Pacific Plate and the formation and expansion of the Philippine Sea Basin. Recent advancements in exploration technologies and theory have been applied to Mesozoic basins in the East China Sea. Researchers have posited that the southern basin has great oil and gas exploration potential. However, the characteristics and evolution of fault structures and their influence on hydrocarbon accumulation remain unclear. Here, in-depth geometric and kinematic analyses of Mesozoic fault structures in the southern ECSB were conducted using the latest interpretations of 2D seismic data and structural analysis theory. The findings revealed that the fault system was well developed and predominantly exhibited multiphase extensional and extensional-torsional features. Based on their lateral distribution and morphology, faults were categorized into three structural styles and seven combinations. According to their developmental timing, periods of active faulting were attributed to the Yanshan and Himalayan epochs. Multiphase fault activities strongly controlled the formation of traps and thus hydrocarbon accumulation, while earlier NE-trending faults controlled the formation of structural belts and hydrocarbon source areas.

The long-term nitrogen fertilizer management strategy based on straw return can improve the productivity of wheat-maize rotation system and reduce carbon emissions by increasing soil carbon and nitrogen sequestration - Ziyan Guo; Yang Liu; Xiangping Meng; Xueni Yang; Chi Ma; Huina Chai; Hui Li; Ruixia Ding; Khudayberdi Nazarov; Xudong Zhang; Qingfang Han (Field Crops Research, 2024)

Reducing fertilization with high planting density increases maize yield stability and nitrogen use efficiency in semi-arid areas - Xiaorong Wu; Zhimin Li; Wenjing Li; Xuanke Xue; Linchuan Yang; Jing Xu; Baoping Yang; Ruixia Ding; Zhikuan Jia; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Adapting to diversified garlic-maize rotation systems by adjusting nitrogen application: Assessing crop yield, nitrogen utilization, and nitrogen footprint - Dan Liu; Qin Mo; Wei Zhang; Wei Lin; Wenjing Li; Maksat Batyrbek; Ruixia Ding; Hui Li; Baoping Yang; Yufeng Zou; Li Wang; Yantai Gan; et al. (Journal of Cleaner Production, 2024)

Nanobubble water promotes anaerobic digestion of high-solids cattle manure under mesophilic and thermophilic conditions - Qingfang Zhang; Ruoyu Wu; Ziying Xu; Yutong Feng; Cheng Peng; Hailong Shi; Yuqian Zhang; Linhai Yang; Dan Luo; Peng Dong; Wenqi Gao; Tianfeng Wang (Environmental Research, 2024)

Driving soil N2O emissions under nitrogen application by soil environmental factor changes in garlic-maize rotation systems - Dan Liu; Chi Ma; Yang Liu; Qin Mo; Wei Lin; Wenjing Li; Hui Li; Baoping Yang; Ruixia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (European Journal of Agronomy, 2024)

Exosomes from porcine serum as endogenous additive maintain function of boar sperm during liquid preservation at 17 °C in vitro - Yang Wang; Qimin Liu; Qingfang Sun; Lijuan Zheng; Tianqi Jin; Heran Cao; Chao Zhu; Long Li; Ye Gong; Fangxia Yang; Wuzi Dong (Theriogenology, 2024)

Shaping the succession patterns of different soil nutrients, enzyme stoichiometry, and microbial communities through rotation systems - Dan Liu; Yang Liu; Junjie Li; Qin Mo; Junyan Tang; Wenhan Liu; Maksat Batyrbek; Tiening Liu; Xudong Zhang; Qingfang Han (CATENA, 2024)

Higher Available Soil Water Storage at Sowing and Frequency of Rainfall Events During the First Month Enhanced the Inhibitory Effect of Nitrification Inhibitor on Nitrous Oxide Emissions - Xiaorong Wu; Junjie Li; Tao Zhang; Xuanke Xue; Shakeel Ahmad; Baoping Yang; Zhikuan Jia; Xudong Zhang; Qingfang Han (Journal of Soil Science and Plant Nutrition, 2024)

Intermittent energization improves anaerobic digestion of microbial electrolysis cell-assisted nitrogen-rich sludge under mesophilic and thermophilic conditions - Qingfang Zhang; Cheng Peng; Jiajia Pu; Yutong Feng; Hong Zhu; Miaozhi Yang; Ziying Xu; Yuqian Zhang; Linhai Yang; Dan Luo; Tianfeng Wang (Journal of Environmental Chemical Engineering, 2024)

Inhibiting N2O emissions and improving environmental benefits by integrating garlic growing in grain production systems - Dan Liu; Hongwei Dong; Chi Ma; Qin Mo; Bo Liu; Ahmad Irshad; Hui Li; Baoping Yang; RuiXia Ding; Altyn Shayakhmetoya; Xudong Zhang; Qingfang Han (Agriculture, Ecosystems & Environment, 2023)

Exploring the relationship between deep roots and shoot growth of wheat under different soil moisture: A large soil column experiment 1 - Dan Liu; Siwei Mou; Yufeng Zou; Baoping Yang; Ruixia Ding; Junfeng Nie; Xudong Zhang; Zhikuan Jia; Qingfang Han (Rhizosphere, 2023)

Testicular miRNAs and tsRNAs provide insight into gene regulation during overwintering and reproduction of Onychostoma macrolepis - Guofan Peng; Chao Zhu; Qingfang Sun; Jincan Li; Yining Chen; Yingjie Guo; Hong Ji; Fangxia Yang; Wuzi Dong (Fish Physiology and Biochemistry, 2022)

Characterization of a Saccharum spontaneum with a basic chromosome number of x = 10 provides new insights on genome evolution in genus Saccharum - Zhuang Meng; Jinlei Han; Yujing Lin; Yiyong Zhao; Qingfang Lin; Xiaokai Ma; Jianping Wang; Muqing Zhang; Liangsheng Zhang; Qinghui Yang; Kai Wang (Theoretical and Applied Genetics, 2020)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Spatial variability of the trends in climatic variables across China during 1961–2010 - Hanbo Yang; Dawen Yang; Qingfang Hu; Huafang Lv (Theoretical and Applied Climatology, 2015)

Multi-scale evaluation of six high-resolution satellite monthly rainfall estimates over a humid region in China with dense rain gauges - Qingfang Hu; Dawen Yang; Zhe Li; Ashok K. Mishra; Yintang Wang; Hanbo Yang (International Journal of Remote Sensing, 2014)

Molecular Characterization of the Full-Length Coding Sequence of the Caprine Laminin Receptor Gene (RPSA) - Rongyan Zhou; Xianglong Li; Huiqin Zheng; Lanhui Li; Weiyao Quan; Zunan Shen; Jun Tong; Qingfang Yang; Qiang Fu (Biochemical Genetics, 2010)

Construction of a molecular functional map of rapeseed (Brassica napus L.) using differentially expressed genes between hybrid and its parents - Yuanyuan Li; Chaozhi Ma; Tingdong Fu; Guangsheng Yang; Jingxing Tu; Qingfang Chen; Tonghua Wang; Xingguo Zhang; Chunyan Li (Euphytica, 2006)